Cover Picture: Inhibition of Mycobacterium tuberculosis Transaminase BioA by Aryl Hydrazines and Hydrazides (ChemBioChem 4/2014). Issue 4 (3rd March 2014) - Dai, Ran; Wilson, Daniel J.; Geders, Todd W.; Aldrich, Courtney C.; Finzel, Barry C.
<x xml:space="preserve">Abstract</x> The cover picture shows crystallographic electron density confirming the formation of a covalent bond between an aryl‐hydrazine inhibitor of Mycobacterium tuberculosis BioA and the pyridoxal phosphate, and a sundering of the bond that normally tethers the co‐factor to the enzyme lysine. On p. 575 ff., B. C. Finzel et al. describe the biochemical and structural characterization of a series of aryl hydrazine and hydrazide inhibitors of this antibacterial drug target. Structural studies describing complexes with inhibitors and substrates included in this report provide a sampling of the conformational states accessible to the flexible enzyme active site, which should be considered in the course of structure‐based drug design. The rarely captured azo‐quinonoid complex arising from reversible inhibition by the aryl hydrazine is unusually stable due to the presence of electronic resonance throughout the adduct. Analogous hydrazides, including the anti‐TB agent isoniazid, form similar covalent adducts, but are ineffective inhibitors because they lack this electronic delocalization.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>